Tower of the Sun, Golden Gate International Exposition, Treasure Island, 1938
Chesley Bonestell, Tower of the Sun, Golden Gate International Exposition, Treasure Island, 1938 oil on canvas Collection of The Oakland Museum. From the exhibition Visionary San Francisco, June 12-August 26 1990, San Francisco Museum of Modern Art.